Advocacy for quantitative progesterone assay in the breeding management of bitches - Oreoluwa Raymond Akinbote; Adedamola Oluwakayode Olanrewaju; Oluropo Michael Obafemi; Samuel Ayodele Famakinde; Akintomiwa Afolarin Bolaji; Mutiat Busayo Rabiu; Oluwadamilare Olufisayo Leigh (Ovozoa: Journal of Animal Reproduction, 2022)
Peripheral progesterone titers characterizing the reproductive cycle of the bitch are fairly well-documented in literature. Progesterone titers obtained via fluorescence-immunoassay technique at different points to the appearance-of-bloody-vulva-discharge (ABVD) in apparently healthy, exotic, multi-breed bitches (n = 76) that were subsequently inseminated were summarized using descriptive statistics. The recommended/predictable progesterone titer-ranges- PPTRs (ng/mL) and modality for insemination(s) were: 7.6-8.5 (inseminate-after-24-hours), 8.6-9.9 (inseminate-after-12-hours) and 10.0-20.0 (inseminate-immediately). The length of days from ABVD to the point of obtaining a PPTR (Mean ± SD) was 12.43 ± 3.38 days (range 8-17 days). The frequencies of progesterone assay per bitch were: one-fold (39.47%), two-fold (39.47%). three-fold (18.43%) and four-fold (2.63%). Observations on pregnancy statuses of bitches based on frequency of progesterone assay(s) were: 57.90% (pregnant, multiple-assay), 5.26% (pregnant, one-fold-assay), 26.32% (not-pregnant, multiple-assay) and 10.52% (not-pregnant, single-assay). The litter sizes at the PPTRs (Mean ± SD) i.e., 7.83 ± 1.86 (7.6-8.5 ng/mL), 7.86 ± 1.73 (8.6-9.9 ng/mL) and 8.83 ± 1.86 (10.0-20.0 ng/mL) were comparable with that for the entire study i.e., 8.16 ± 1.87. Similarly, the range of litter sizes at the three PPTRs as well as that for the entire study were same i.e., 5-10 puppies. It is concluded as follows: multiple progesterone assays resulted in higher pregnancy outcome and, litter sizes were not affected as long as insemination(s) occurred within the recommended progesterone titer-ranges. We recommend a comprehensive investigation of all pregnancy determinants, even for apparently healthy dogs, by dog-lovers and, regarding progesterone, multiple-assays, rather than one-fold assay, will upscale their breeding business.